Short-term intensive training attenuates the exercise-induced interaction of mono-1/2 cells and platelets after coronary bypass in cardiac patients - Huang, Shu-Chun; Wong, Mei-Kuen; Lin, Pyng-Jing; Tsai, Feng-Chun; Chu, Jaw-Ji; Wu, Meng-Yu; Fu, Tieh-Cheng; Wang, Jong-Shyan (Thrombosis and Haemostasis, 2017)
The interaction between platelets and monocytes plays a critical role in the pathogenesis and progression of cardiovascular diseases. This study investigated how short-term intensive training (SIT) influences monocyte subset characteristics and exercise-induced monocyte and platelet aggregates (MPAs) following elective coronary bypass (CABG) in cardiac patients. Forty-nine patients hospitalised for CABG were randomised into SIT (N=26) and conventional training (CT, N=23) groups. The SIT subjects underwent supervised aerobic training at 80∼120 % of the ventilatory anaerobic threshold based on sub-maximal exercise tests performed 7 days post-CABG for 20 sessions with two sessions/day and 30 min/session, which were completed within four weeks after surgery. The CT subjects performed light-intensity conditioning exercise for ≤4 sessions. Resting and maximal exercise-mediated monocyte characteristics and MPA were determined before and following intervention. The SIT group had a larger improvement in ventilation efficiency and anaerobic threshold than the CT group; the SIT group exhibited larger reductions in blood monocyte subtypes 1 and 2 (Mono1 and 2) counts at rest than the CT group; the SIT group but not the CT group exhibited attenuated formation of Mono1/platelet hetero-aggregation (MPA1) and CD42b expression on Mono1/2 caused by strenuous exercise; and plasma levels of macrophage inflammatory protein-1β and soluble P-selectin showed similar trends as Mono1/2 and MPA1, respectively. In conclusion, SIT modestly improved aerobic capacity in patients following CABG. Moreover, SIT simultaneously ameliorated the CD42b expression of Mono1/2 cells and maximal exercise-induced MPA1, which may reduce the risk of inflammatory thrombosis.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Exercise; coronary artery bypass; monocyte; monocyte-platelet aggregates; platelet; inflammation